2022
DOI: 10.3390/ijerph19031222
|View full text |Cite
|
Sign up to set email alerts
|

Different Roles of Rumination and Mindfulness among Cyber-Ostracized Adolescents’ Psychological Well-Being

Abstract: Previous research has confirmed the harmful effects of cyber-ostracism on adolescents. However, research that has investigated the effect of cyber-ostracism on adolescents’ psychological well-being and the underlying mechanisms of this influence remains scarce. Using a sample of 421 Chinese adolescents, this study examined the short-term effect of cyber-ostracism on adolescents’ psychological well-being, along with the mediating effect of rumination. Mindfulness is considered as a moderator influencing this un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…In this study, the relationship between mindfulness and psychological well-being was confirmed. This result is consistent with those of previous research [ 13 – 17 ]. Huang et al (2021) reported a positive relationship between mindfulness and psychological well-being in a group of college students [ 14 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study, the relationship between mindfulness and psychological well-being was confirmed. This result is consistent with those of previous research [ 13 – 17 ]. Huang et al (2021) reported a positive relationship between mindfulness and psychological well-being in a group of college students [ 14 ].…”
Section: Discussionsupporting
confidence: 94%
“…Psychological well-being during adolescence is vital and one of the most important determinants of mental health in adulthood. Previous research has supported the relationship between mindfulness and psychological well-being [ 14 , 17 ]. The focus of this study is to explain this relationship by studying the mediating role of three variables: self-compassion, cognitive flexibility and emotional dysregulation.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The reduction in the possibilities for face-to-face interaction, lockdowns and social distancing (Nurunnabi et al, 2021;Viner et al, 2021), increased uncertainty about the future, financial implications (Cao et al, 2020;Russo and Terraneo, 2020), health and mental health risks (Son et al, 2020;Browning et al, 2021;Fruehwirth et al, 2021;Křeménková et al, 2021;Xu et al, 2021) as well as the inevitability of having to spend a great amount of time online which is also flooded with more negative content (Ratan et al, 2021;Serra et al, 2021) may play a role in the increased development of mobile phone addiction and the magnification of its negative consequences and mental health issues in general, especially in individuals who have less resources to cope with challenging situations and adversities. Surprisingly, although previous studies have both described the mediating role of rumination in the context of mobile phone addiction (Wang et al, 2018;Lian et al, 2021;Liu et al, 2021;Li et al, 2022;Peng et al, 2022) and have indicated cross-cultural differences in perceived stress (Lee et al, 2022;Mohamed et al, 2022), ruminative thinking (Murdock et al, 2019) and mobile phone addiction (Yang et al, 2019;Olson et al, 2022), there is no direct evidence available on the cultural conditioning of this mediating relationship. To explore the above-mentioned mechanism and in part fill the gap in understanding the role of cross-cultural differences, the aim of this study was to examine the mediating role of ruminative thinking on the relationship between mobile phone addiction and perceived stress in two different cultural settings and to compare them against each other.…”
Section: Introductionmentioning
confidence: 98%